Proximate composition of wild yam Dioscorea praehensilis Tubers flours as Influenced by Boiling Times (Journal of Basic and Applied Research in Biomedicine, 2022)
The wild yam Dioscorea praehensilis is widely consumed as famine food in Côte d’Ivoire and numbers of African countries mainly after boiling. Raw and boiled wild yam tubers (Dioscorea praehensilis) flours were analyzed for proximate contents such as ash, crude protein, carbohydrate, Moisture energy s using standard procedures and methods. (YT0) was used as control compared to tubers boiled for 5 minutes (YT5), 10 minutes (YT10), 20 minutes (YT20), 30 minutes (YT30) and 40 minutes (YT40). The crude protein contents (9.13 g/100g DM), ash (1.02 g/100g DM), lipid (3.25 g/100g DM), carbohydrate (89.21 g/100g DM) and Moisture (13.04%) were significantly (p